Menginspirasi Generasi Muda: Membuat Tong Sampah dan Mendidik Remaja dalam Menjaga Kebersihan Lingkungan - Masbullah, Masbullah; Bahri, Salmi Yuniar; Juhad, Moh.; Saifurruhaidi, Saifurruhaidi (Journal of Community Service and Society Empowerment, 2023)
Environmental cleanliness plays a crucial role in disease prevention efforts. Without attention to environmental cleanliness, this pandemic will never end. This community service program aims to (1) instill awareness of the importance of environmental cleanliness from adolescence, (2) enhance understanding of the significance of maintaining environmental cleanliness and health, and (3) teach the habit of proper waste disposal. The goal is to create a comfortable, clean, healthy, and beautiful environment for teenagers to play and learn. To achieve this goal, the program employs several methods. The first phase is an approach where the service team adapts to teenagers. The second phase involves setting an example of proper waste disposal. The third phase provides guidance and education on the importance of environmental cleanliness and its consequences if neglected. One of the major issues in this environment is the lack of public waste bins, which gives teenagers an excuse not to dispose of trash properly. To address this problem, the fourth phase involves the creation of trash bins to be placed in public areas and mosques, along with organizing community clean-up activities. Finally, the evaluation phase is used to measure the program's success among teenagers in the Dusun Mandar Desa Labuhan Haji. The results of this program show that teenagers in the community now have an understanding and a caring attitude towards the environment.